Encrypted Wireless (En-Fi) - Azmi, Adif Asyraf (Journal of Computing Technologies and Creative Content, 2019)
Public Wi-Fi have been known for numerous opportunity for attackers to steal information from user connected to it. User data will be leak if not protected while using public Wi-Fi. Other than that, the router itself isn’t protected which mean other user can sniff out the admin username and password thus gaining full control over the router. This project is designing to counteract that problem by using VPN service to encrypted data throughout the network and encrypting the router web interface.